Number 24 (November 1991) - Southern Fishes Council (Southeastern Fishes Council Proceedings, 1991)
(November 1991) - Fishes of the Sucarnoochee River System Alabama and Mississippi. By W.D. Hubbard, et al., 11 pp. Provenance and Disposition of Fish Specimens Appearing in Color Plates of Kuehne and A. Barbour's Book, The American Darters. By C.R. Gilbert and S.J. Walsh, 8 pp. Museum Notes by E.G. Maurakis, 1 pp.
Keywords: fishes; sucarnoochee river; kuehne